Telegram as a Digital Learning Tool: Transforming Language Education - Mohamed Idris, Mohammad Talha; Norliza Ghazali; Ruhil Amal Azmuddin (Journal of Social Transformation and Regional Development, 2025)
The integration of digital technologies into learning environments enables more efficient coordination between teachers and learners, overcoming physical and temporal barriers that often limit access to educational opportunities. This study investigates the use of Telegram as a mobile-based digital learning tool (DLT) to support undergraduate students in English language learning. Specifically, it examines learners’ perceptions of Telegram’s role in facilitating language acquisition and identifies challenges encountered during its use. Language learning materials were delivered through Telegram, accompanied by guided online discussions. Undergraduate participants were engaged with the materials, completed questionnaires, and participated in semi-structured interviews conducted via the online learning platform. Findings indicate that Telegram provides accessible English communication materials that promote frequent practices and sustained exposure to new language input. Its flexible, self-paced structure helped reduce time and space constraints, enabling deeper comprehension of learning content for the learners. Despite minor challenges related to engagement and navigation issues, learners perceived Telegram as a valuable support for language development. The study recommends broader institutional adoption of decentralized and accessible digital tools to enhance linguistic instructions and align teaching practices with contemporary technological advancements.